Analisis Manajemen Keuangan Yayasan Pendidikan Sekolah Prabumulih dalam Meningkatkan Efektivitas Penggunaan Dana Operasional Sekolah - Nurfatidah, Sri; Maryani, Maryani (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to analyze the financial management system implemented by the Educational Foundation of Sekolah Prabumulih and assess its effectiveness in utilizing operational funds. Using a qualitative descriptive approach with a case study method, the research explores key processes including financial planning, budget implementation, internal control, and financial evaluation. Data were collected through in-depth interviews, direct observations, and documentation analysis involving foundation administrators, school principals, and finance staff. The findings reveal that although the foundation conducts annual financial planning through the preparation of a school budget (RAPBS), the process lacks participation from broader school stakeholders. Budget implementation often deviates from the plan, with most expenditures focused on routine operational costs, while educational quality improvement programs are underfunded. Internal control mechanisms are weak, with limited oversight and no regular internal audits. Furthermore, financial evaluations are infrequent and transparency toward external parties such as parents or school committees remains low. The study concludes that ineffective financial management marked by limited participation, weak control, and lack of transparency has hindered the optimal use of operational funds. Improvements in participatory budgeting, disciplined implementation, structured internal control, and open financial reporting are crucial to enhance fund effectiveness and support better educational outcomes.